Internalisasi Nilai-Nilai Moral melalui Pembelajaran Pendidikan Agama Islam dalam Menghadapi Tantangan Era Milenial di MTs Dharut Tholibin: Instilling Moral Values in Islamic Religious Education Learning Facing the Millennial Era at MTs Dharut Tholibin - Imam Rohani; Hallil Abdulloh; M. Dini Abdillah; Misbahul Munir (Educan, 2025)
This research examines the cultivation of moral values in Islamic Religious Education learning to face the millennial era at MTs Dharut Tholibin. The research aims to analyze strategies, methods, and challenges in instilling moral values to millennial generation students. The study employs a qualitative approach with a case study method. Data collection was conducted through learning observation, in-depth interviews with Islamic Education teachers, school principal, and students, as well as documentation study. The results show that moral values cultivation is implemented through integration of digital technology with traditional learning, role modeling, religious practice habituation, and mentoring programs. Challenges faced include social media influence, digital lifestyle, and declining student interest in conventional learning. Adaptive strategies implemented include the use of digital learning media, interactive discussions on contemporary issues, and learning approaches relevant to students' lives. This research contributes to the development of effective Islamic Religious Education learning models for shaping the character of the millennial generation.